2022
DOI: 10.3389/fsurg.2022.990749
|View full text |Cite
|
Sign up to set email alerts
|

TIMM13 as a prognostic biomarker and associated with immune infiltration in skin cutaneous melanoma (SKCM)

Abstract: ObjectiveProviding protection against aggregation and guiding hydrophobic precursors through the mitochondria’s intermembrane space, this protein functions as a chaperone-like protein. SLC25A12 is imported by TIMM8 as a result of its interaction with TIMM13. In spite of this, it is still unknown how TIMM13 interacts with skin cutaneous melanoma (SKCM) and tumor-infiltrating lymphocytes (TILs).MethodsAberrant expression of TIMM13 in SKCM and its clinical outcome was evaluated with the help of multiple databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Recently, Kim et al found that Timm13 showed reduced expression in human Alzheimer's disease brain tissues [45]. The latest research demonstrated that the expression of Timm13 in cutaneous melanoma (SKCM) tissues was higher than that in adjacent tissues, and Timm13 expression was closely related to programmed cell death protein 1 (PD1), suggesting that it might regulate the tumor immune microenvironment and affect prognosis [46]. Research on the relationship between translocase of the mitochondrial inner membrane and various diseases has gradually increased and several articles have reported on Timm13 in the past two years.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al found that Timm13 showed reduced expression in human Alzheimer's disease brain tissues [45]. The latest research demonstrated that the expression of Timm13 in cutaneous melanoma (SKCM) tissues was higher than that in adjacent tissues, and Timm13 expression was closely related to programmed cell death protein 1 (PD1), suggesting that it might regulate the tumor immune microenvironment and affect prognosis [46]. Research on the relationship between translocase of the mitochondrial inner membrane and various diseases has gradually increased and several articles have reported on Timm13 in the past two years.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression of HSPB1 in different cancer types was analysed in the TIMER database (4 January 2023) (http://cistrome.org/TIMER/) [12] and Xiantao online tools (4 January 2023) (https://www.xiantao.love) [13]. The protein expression of HSPB1 in different cancer types was analysed in the Human Protein Atlas database (5 January 2023) (https://www.proteinatlas.org/) [14].…”
Section: Hspb1 Expression In Pan-cancersmentioning
confidence: 99%
“…The correlation between HSPB1 expression and survival in pan-cancers was analysed in the Xiantao online tools (6 January 2023) (https://www.xiantao.love) [13].…”
Section: Survival Analysis In Pan-cancersmentioning
confidence: 99%